Microhabitat use and thermoregulation in Sceloporus horridus horridus (Wiegmann 1939) (Sauria: Phrynosomatidae) - Bustos Zagal, María Guadalupe; Manjarrez, Javier; Castro-Franco, Rubén (Instituto de Ecología, A.C., 2013)
This paper examines the use of different microhabitats throughout the day, year, by sex, by age, at different intervals of altitude and its implications for thermoregulation and conservation. Overall 49.5% of the lizards used trees, 32.62% rocks and less often 2.3% shrubs (?2 = 216.06, gl 3, p < 0.05). The analysis of microhabitat used by sex revealed significant differences among young, female, and male (?2 = 7.24, gl 6, p < 0.05). The young females most often used rocks, while subadults and adults preferred to use trees (?2 = 13.38, gl 6, p < 0.05). In males, subadults and young used rocks, and adults trees (?2 = 15.22, gl 4, p < 0.05).The altitudinal distribution has an effect on habitat use; in the altitudinal range of 800 to 1,100 m these lizards have a tendency to be more arboreal, and between 1,100 and 1,400 m more frequently used rocks (?2 = 36.21, gl 6, p < 0.05). In the dry season there was a significant difference in the use of microhabitats between 9:00 and 14:00 hours, with the highest number of sightings on trees and rocks. In the rainy season there was no significant difference in the analysis of microhabitat use over the hours of the day. The average body temperature was 33.52 °C (22.0-39.0 ± 2.9). There were no significant differences in body temperature of lizards in different microhabitats. Cloacal temperatures in all microhabitats were 2 °C and 3 °C higher than air temperatures and substrate. Most sightings were between 10:00 and 15:00 hours so this species is considered a diurnal lizard showing thigmothermy and heliothermy. There were significant differences (F1,414 = 5.0918, p = 0.024561) in the lizard cloacal temperatures between the rainy (33.2 °C ± 3.17, n = 215) and dry seasons (34.2 °C ± 5.4, n = 201). Trees are important for thermoregulation in this species; however, even though these lizards could live in deforested areas, they might encounter thermoregulatory difficulties due to reduced periods of activity.